(3TQM bGfhf GHf SjfGs - (3YdGA GdOjf Ydj Hf CHi GdMRe GdbQTi ,GHf GdfajSs; (3GdQFjS GHf SjfG , CHh Ydj TQa Gdedc (B: (3GdajdSha GdQFjS,J (B428 (3g` s
(3ChdgG (B:s
(3Gdaf GdQGHY YTQ ai GdcHO hGMhGdgG ,hgh CQHY ebGdGJ ,GdChdi ai cdjGJ CMhGd GdcHO ,hEf JTQjM GdcHO hefaYJgG s
(3BNQgG (B:s
(3Ef gPG GdeYLhf eSGh ai GdbhI ddeYLhf GdgfOi ,hgh jbhi GdeYOI CjVkG hEf HGbi GdcdGe ai gPG GdcJGH XGgQ ,hGddg CYde s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGdKs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
Keywords: (3GdWHs